Ação antifúngica de produtos naturais e derivados, utilizados na candidíase bucal em modelo animal: uma revisão sistemática - Costa Neto, Raimundo Euzébio da (2023)
Introduction: Oral candidiasis is one of the most common fungal infections in clinical dental practice and its establishment is due to factors related to the immune status of the host and to virulence conditions of pathogen. Several natural products and their derivatives are studies in the control of fungal infections in vitro and few of these studies have advanced to studies in in vivo models. The need to study new antifungals is supported by the increasing isolation of strains with low sensitivity and others with a resistance profile to the available antifungals for oral candidiasis conventional treatment. Objectives: To carry out a systematic review of the literature, seeking to evaluate the antifungal action of natural products as possible candidates for oral candidiasis alternative treatments, with emphasis on the use of animal models of infection, as well as to investigate the cytotoxic effects of these bioactive compounds. Methods: A systematic search was carried out in accordance with PRISMA guidelines, using a pre-established search strategy, with three hundred and thirty references retrieved after removing duplicates. Two reviewers performed the screening of articles included in the final review according to eligibility criteria, risk of bias assessment - SYRCLE tool. Data extraction was performed independently and when there was any disagreement between the pairs, another reviewer was consulted. Results: Twenty-two articles were included in the qualitative analysis. The isolated compounds were the most studied (13 articles, 50%), followed by the associated isolated compounds (5 articles, 19%) and the crude extracts (4 articles, 15%), fractionated extracts (2 articles, 8%) and the essential oils (2 articles, 8%). Only five studies performed cytotoxicity tests. The compounds showed low MIC values and therapeutic effects in the tested animal model.Conclusion: The most promising compounds with antifungal activity were ellargic acid associated with 2-hydroxypropyl-β-cyclodextrin, caffeic acid phenethyl ester, the ethyl acetate fraction of the Eugenia uniflora extract, the Punica granatum extract and the nanoencapsulated extract of Erodium glaucophyllum.